2013
DOI: 10.1002/14651858.cd002817.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy versus placebo or no intervention in Parkinson's disease

Abstract: Background Despite medical therapies and surgical interventions for Parkinson's disease (PD), patients develop progressive disability. Physiotherapy aims to maximise functional ability and minimise secondary complications through movement rehabilitation within a context of education and support for the whole person. The overall aim is to optimise independence, safety, and well-being, thereby enhancing quality of life. Objectives To assess the e ectiveness of physiotherapy intervention compared with no interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
106
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 247 publications
(113 citation statements)
references
References 108 publications
6
106
0
1
Order By: Relevance
“…Many factors remain unknown as to the best format of physiotherapy to use in PD, including the frequency, intensity, duration, and setting (such as home vs group based). 160 Determining the relative benefit of one type of exercise therapy over another remains a challenge. The majority of studies reviewed evaluated two active types of exercise, and in most cases both interventions were positive compared to baseline measures.…”
Section: Symptomatic Adjunct Therapy To Levodopa For Specific or Genementioning
confidence: 99%
“…Many factors remain unknown as to the best format of physiotherapy to use in PD, including the frequency, intensity, duration, and setting (such as home vs group based). 160 Determining the relative benefit of one type of exercise therapy over another remains a challenge. The majority of studies reviewed evaluated two active types of exercise, and in most cases both interventions were positive compared to baseline measures.…”
Section: Symptomatic Adjunct Therapy To Levodopa For Specific or Genementioning
confidence: 99%
“…There is clear evidence from a number of systematic reviews that exercise improves the following 2 key physical risk factors for falls: poor balance and decreased mobility. 68,69,96 Furthermore, exercise does not increase the overall risk of falls. The findings of the exercise trials suggest that exercise interventions delivered early in the disease process are effective in reducing falls in a cost-effective manner.…”
Section: What Can Be Recommended At This Stage?mentioning
confidence: 99%
“…8,9 In addition to dopaminergic medication, rehabilitation was found to improve motor function in the short term in PD patients. 10 This entails relearning of a known motor skill through intensive practice. However, as the basal ganglia are a key hub in the motor learning network, 11 it was suggested that consolidation of learning, often hallmarked by automatization, transfer, and retention, may be affected in PD.…”
mentioning
confidence: 99%